Human Resource Management Analysis (Hospital Nurse Performance Case Study) - Nasrullah Nasrullah; Riski Dwi Prameswari (Sean Institute, 2023)
Organizations such as Regional General Hospitals (RSUD) are inseparable from implementing human resource management to take advantage of every opportunity to achieve organizational goals. In this study, the author analyzed the hospital's human resource management application. The purpose of this study is to find out the factors that become the study of the RSUD in the application of management analysis of the application of human resources in organizations. This research method is a descriptive qualitative method. The data in this study was obtained by interview, observation, and secondary data techniques from the hospital. The results of this study show that RSUD has implemented ISO 31000-based human resource management and compiled it by considering balance scorecards and key performance indicator factors.